Positive active material for rechargeable lithium battery, preparing method thereof and rechargeable lithium battery including the same

KR103020685B1Active Publication Date: 2026-09-16SAMSUNG SDI CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020230123254
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-12-07
Filing Date
2023-09-15
Publication Date
2026-09-16
Estimated Expiration
2043-09-15

Smart Images

  • Figure 112023102500232-PAT00003_ABST
    Figure 112023102500232-PAT00003_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material for a lithium secondary battery comprising a first positive electrode active material in the form of a secondary particle formed by the aggregation of a plurality of primary particles, and a second positive electrode active material in the form of a single particle, wherein the first positive electrode active material and the second positive electrode active material each comprise a lithium nickel-based composite oxide having a nickel content of 70 mol% or more relative to all elements excluding lithium and oxygen, the first positive electrode active material comprises a coating portion existing in the form of a film on the surface of the secondary particle, and the second positive electrode active material comprises a coating portion existing in the form of a film on the surface of the single particle, wherein the coating portion of the first positive electrode active material and the coating portion of the second positive electrode active material each comprise lithium cobalt oxide and cobalt oxyhydroxide, the positive electrode active material for a lithium secondary battery, a method for manufacturing the same, and a lithium secondary battery comprising the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The invention relates to a positive electrode active material for a lithium secondary battery, a method for manufacturing the same, and a lithium secondary battery containing the same. Background Technology

[0002] Lithium-ion batteries, which offer high energy density and portability, are primarily used as the power source for mobile information terminals such as mobile phones, laptops, and smartphones. Recently, active research is being conducted to utilize high-energy-density lithium-ion batteries as power sources for driving or energy storage in hybrid and electric vehicles.

[0003] Various cathode active materials are being investigated to realize lithium secondary batteries suitable for these applications. Among them, lithium nickel-based oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides, and lithium cobalt oxides are primarily used as cathode active materials. However, these cathode active materials face problems such as structural collapse or cracking due to repeated charge-discharge cycles, which degrades the long-term lifespan of the lithium secondary battery and increases resistance, resulting in unsatisfactory capacity characteristics. Therefore, there is a need to develop new cathode active materials that can secure long-term lifespan characteristics while achieving high capacity and high energy density. The problem to be solved

[0004] It increases the energy density of high-nickel cathode active materials while improving long lifespan and thermal stability characteristics. means of solving the problem

[0005] In one embodiment, a positive active material for a lithium secondary battery is provided, comprising a first positive active material in the form of a secondary particle formed by the aggregation of a plurality of primary particles, and a second positive active material in the form of a single particle, wherein the first positive active material and the second positive active material each comprise a lithium nickel-based composite oxide having a nickel content of 70 mol% or more relative to all elements excluding lithium and oxygen, the first positive active material comprises a coating portion existing in the form of a film on the surface of the secondary particle, and the second positive active material comprises a coating portion existing in the form of a film on the surface of the single particle, wherein the coating portion of the first positive active material and the coating portion of the second positive active material each comprise lithium cobalt oxide and cobalt oxyhydroxide.

[0006] In another embodiment, a method for manufacturing a positive electrode active material for a lithium secondary battery is provided, comprising: a first positive electrode active material in the form of secondary particles formed by aggregating a plurality of primary particles containing a lithium nickel-based composite oxide having a nickel content of 70 mol% or more relative to all elements excluding lithium and oxygen; a second positive electrode active material in the form of a single particle containing a lithium nickel-based composite oxide having a nickel content of 70 mol% or more relative to all elements excluding lithium and oxygen; cobalt sulfate; and sodium hydroxide being introduced into a solvent and mixed; removing the solvent; adding a lithium raw material to the product; and heat treating to obtain the aforementioned positive electrode active material.

[0007] In another embodiment, a lithium secondary battery comprising a positive electrode and a negative electrode and an electrolyte is provided, comprising the positive electrode active material. Effects of the invention

[0008] A positive electrode active material for a lithium secondary battery according to one embodiment achieves high capacity and high energy density while enhancing stability, and a lithium secondary battery containing the same has improved high-temperature long-life characteristics and thermal stability. Brief explanation of the drawing

[0009] FIG. 1 is a schematic diagram illustrating a lithium secondary battery according to one embodiment. Figure 2 is an X-ray diffraction (XRD) analysis graph of the positive electrode active material prepared in Example 1, the positive electrode plate before life, and the positive electrode plate after life. Figure 3 is an enlarged view of the graph at around 20° in Figure 2. Figure 4 is an enlarged view of the graph near 40° in Figure 2. Figure 5 is an X-ray diffraction analysis graph for Co(OH)2, CoOOH, and Co3O4. Figure 6 is an image highlighting the cobalt element by SEM-EDS analysis on the fracture surface of the first positive electrode active material of Example 1. Figure 7 is an image highlighting the cobalt element by SEM-EDS analysis on the fracture surface of the second positive electrode active material of Example 1. Figure 8 is a graph evaluating the life characteristics of the coated half-cells prepared in Example 1, Comparative Example 1, and Comparative Example 2. Specific details for implementing the invention

[0010] Specific embodiments are described below in detail so that those skilled in the art can easily implement them. However, the present invention may be implemented in various different forms and is not limited to the embodiments described herein.

[0011] The terms used herein are for describing exemplary embodiments only and are not intended to limit the invention. Singular expressions include plural expressions unless the context clearly indicates otherwise.

[0012] Here, "combinations of these" refers to mixtures of components, laminates, composites, copolymers, alloys, blends, reaction products, etc.

[0013] The terms "include," "equip," or "have" used herein are intended to specify the existence of the implemented features, numbers, steps, components, or combinations thereof, and should be understood as not excluding in advance the existence or addition of one or more other features, numbers, steps, components, or combinations thereof.

[0014] In the drawings, thicknesses have been enlarged to clearly represent various layers and regions, and the same reference numerals have been used for similar parts throughout the specification. When a part such as a layer, film, region, or plate is described as being "on" or "on" another part, this includes not only cases where it is "immediately on" another part, but also cases where there is another part in between. Conversely, when a part is described as being "immediately on" another part, it means that there is no other part in between.

[0015] In addition, the term “layer” here includes not only the shape formed on the entire surface when viewed in a plan view, but also the shape formed on some surfaces.

[0016] In addition, the average particle size can be measured by methods widely known to those skilled in the art, for example, by measuring with a particle size analyzer, or by measuring with transmission electron microscope images or scanning electron microscope images. Alternatively, the average particle size value can be obtained by measuring using dynamic light scattering and performing data analysis to count the number of particles for each particle size range and then calculating from thereon. Unless otherwise defined, the average particle size may refer to the diameter (D50) of a particle whose cumulative volume in the particle size distribution is 50% by volume.

[0017] Here, “or” is not interpreted in an exclusive sense; for example, “A or B” is interpreted to include A, B, A+B, etc.

[0018] positive electrode active material

[0019] In one embodiment, a positive electrode active material for a lithium secondary battery is provided, comprising a first positive electrode active material in the form of a secondary particle formed by the aggregation of a plurality of primary particles, and a second positive electrode active material in the form of a single particle.

[0020] The first positive active material and the second positive active material each comprise a lithium nickel-based composite oxide having a nickel content of 70 mol% or more relative to all elements excluding lithium and oxygen. That is, the first positive active material and the second positive active material can be described as high-nickel positive active materials.

[0021] In addition, the first positive active material includes a coating portion existing in the form of a film on the surface of the secondary particle, and the second positive active material includes a coating portion existing in the form of a film on the surface of the single particle. Here, the coating portion of the first positive active material and the coating portion of the second positive active material are each characterized by comprising lithium cobalt oxide (LiCoO2) and cobalt oxyhydroxide (CoOOH).

[0022] In the above coating portion, the cobalt oxyhydroxide has an R-3m crystal structure, which facilitates lithium migration with minimal structural heterogeneity with the lithium nickel-based composite oxide, thereby improving the performance of the lithium secondary battery.

[0023] The above coating portion may be said to include a composite phase of lithium cobalt oxide and cobalt oxyhydroxide. Through this composite phase, the surface structure of the cathode active material can be strengthened, thereby suppressing side reactions between the cathode active material and the electrolyte, and improving the lifespan characteristics, overcharge characteristics, and high-temperature storage characteristics of the lithium secondary battery. Through the above composite phase, the unstable structure of high-nickel cathode active materials can be overcome, thereby securing stable characteristics at the level of low-nickel cathode active materials.

[0024] The above composite phase can be confirmed through X-ray diffraction analysis of the positive electrode active material or the positive electrode plate. For example, the positive electrode active material may show peaks at 19.5° to 20.5° and 39° to 40° in X-ray diffraction analysis, and these peaks may indicate the presence of cobalt oxyhydroxide.

[0025] The above coating portion exists in the form of a film, which may be in the form of a continuous coating layer or an island, and is distinguished from existing in the form of particles.

[0026] The thickness of each of the coating portion of the first positive active material and the coating portion of the second positive active material may be 1 nm to 500 nm, for example, 1 nm to 400 nm, 1 nm to 300 nm, 1 nm to 200 nm, 1 nm to 100 nm, 5 nm to 50 nm, or 5 nm to 40 nm. By forming the coating portion within this thickness range, the structure of the positive active material can be stabilized and side reactions with the electrolyte suppressed, thereby improving the performance of the lithium secondary battery without acting as a resistor or degrading battery performance. Here, the thickness of the coating portion may be measured by SEM, TEM, TOF-SIMS, XPS, or EDS, and, for example, through an SEM image of a cross- section of the positive active material.

[0027] The cobalt content of the coating portion in the above-mentioned positive electrode active material may be about 0.5 mol% to 5 mol%. Specifically, in the entire positive electrode active material, the content of surface cobalt relative to 100 mol% of elements excluding lithium and oxygen in the lithium nickel-based composite oxide may be 0.5 mol% to 5 mol%, for example, 0.5 mol% to 4 mol%, or 1 mol% to 3 mol%. By coating with cobalt at the above content, the structure of the positive electrode active material can be stabilized without reducing capacity, and the efficiency and lifespan characteristics of the battery can be improved.

[0028] Meanwhile, according to one embodiment, the ratio of the content of cobalt (at%) relative to the total amount of nickel and cobalt in the coating portion of the first positive active material to the content of cobalt (at%) relative to the total amount of nickel and cobalt in the coating portion of the second positive active material may be 1.45 to 1.60. When a coating portion is formed on each of the positive active materials in a mixed form of a first positive active material in the form of secondary particles and a second positive active material in the form of single particles, an imbalance in coating between the two particles occurs. For example, when two types of particles are mixed and simultaneously wet-coated with cobalt, there is a tendency for more coating material to react and be coated on the single particles, which have a relatively high specific surface area. Consequently, the secondary particles do not obtain a sufficient coating effect, leading to structural collapse or side reactions on the surface, which accelerates degradation; the uneven presence of coating particles on the surface causes gas generation; and the excessive coating on the single particles acts as resistance, adversely affecting battery performance. On the other hand, according to one embodiment, the performance of a lithium secondary battery, such as high-temperature long-term life characteristics, can be improved by suppressing excessive coating on a single particle while strengthening the coating of a secondary particle, that is, by appropriately adjusting the relationship between the coating content of the two types of particles. For example, when the ratio of the cobalt coating content of the first cathode active material to the cobalt coating content of the second cathode active material satisfies 1.45 to 1.60, high capacity and high energy density can be achieved while simultaneously improving high-temperature long-term life characteristics, suppressing the amount of gas generated during high-temperature storage, and improving initial charge-discharge efficiency. The above ratio may be, for example, 1.45 to 1.55 times, or 1.50 to 1.60 times.

[0029] First positive active material

[0030] The first positive electrode active material is in the form of a polycrystalline structure and comprises secondary particles formed by the aggregation of at least two primary particles. The first positive electrode active material according to one embodiment comprises a coating portion existing in the form of a film along the surface of the secondary particles and comprises a composite phase of lithium cobalt oxide and cobalt oxyhydroxide.

[0031] The content of cobalt relative to the total amount of nickel and cobalt in the cobalt coating portion of the first positive active material may be 55 at% to 70 at%, for example, 55 at% to 68 at%, 55 at% to 65 at%, 55 at% to 63 at%, 57 at% to 70 at%, 59 at% to 70 at%, 60 at% to 70 at%, 60 at% to 65 at%, or 61 at% to 63 at%. When the cobalt coating content of the first positive active material satisfies the above range and satisfies 1.45 to 1.60 times the cobalt coating content of the second positive active material, non-uniformity of coating between particles is eliminated, and a uniform coating is formed on the surface of the first positive active material, thereby suppressing gas generation and improving initial charge / discharge efficiency and long-term life characteristics.

[0032] The first positive active material according to one embodiment may further include a grain boundary cobalt coating portion located on the surface of primary particles inside the secondary particles. The grain boundary cobalt coating portion exists inside rather than on the surface of the secondary particles, and can be described as being coated along the interface of the primary particles inside the secondary particles, and thus can be expressed as being coated on the grain boundaries. Here, the inside of the secondary particles refers to the entire interior excluding the surface, and may, for example, refer to the entire interior from a depth of approximately 10 nm from the outer surface, or the region from a depth of 10 nm to a depth of about 2 μm. By further including the grain boundary cobalt coating portion in the first positive active material according to one embodiment, structural stability is enhanced, a uniform and even coating is induced on the surface, and the coating content on the surface is appropriately controlled, thereby improving initial charge / discharge efficiency and lifespan characteristics without increasing resistance.

[0033] The average particle size of the first positive active material, that is, the average particle size of the secondary particle, may be 5 μm to 20 μm. For example, it may be 7 μm to 20 μm, 10 μm to 20 μm, or 12 μm to 18 μm. The average particle size of the secondary particle of the first positive active material may be larger than the average particle size of the second positive active material of a single particle, which will be described later. The positive active material according to one embodiment may be in the form of a mixture of the first positive active material, which is polycrystalline and covalent, and the second positive active material, which is a single particle and subparticle, thereby improving the density of the mixture and enabling high capacity and high energy density. Here, the average particle size of the first positive active material may be obtained by randomly selecting about 20 active materials in the form of secondary particles from an electron microscope image of the positive active material, measuring their particle sizes, and taking the diameter (D50) of the particle with a cumulative volume of 50% of the particle size distribution as the average particle size.

[0034] The first cathode active material may be a high-nickel cathode active material containing a high amount of nickel. In the lithium nickel-based composite oxide, the nickel content may be 70 mol% or more based on the total amount of elements excluding lithium and oxygen, for example, 75 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, and 99.9 mol% or less, or 99 mol% or less. Such a high-nickel first cathode active material can achieve high capacity and high performance.

[0035] Second positive active material

[0036] The second positive electrode active material is in the form of a single particle, which means that it exists alone without grain boundaries within the particle and is composed of a single particle. Morphologically, it may refer to a single particle, a monolith structure, a monolithic structure, or a non-aggregated particle existing in an independent phase where the particles are not mutually aggregated, and as an example, it may be a single crystal. The positive electrode active material according to one embodiment can achieve high capacity and high energy density while exhibiting improved lifespan characteristics by including the second positive electrode active material in the form of such a single particle.

[0037] A second positive active material according to one embodiment includes a film-shaped coating portion formed along the surface of a single particle, and the coating portion includes a composite phase of lithium cobalt oxide and cobalt oxyhydroxide.

[0038] The content of cobalt relative to the total amount of nickel and cobalt in the coating portion of the second positive active material may be 39 at% to 45 at%, for example, 39 at% to 44 at%, 39 at% to 43 at%, 39 at% to 42 at%, 40 at% to 45 at%, or 41 at% to 45 at%. When the cobalt coating content of the second positive active material satisfies the above range, and the ratio of the cobalt coating content of the first positive active material to it satisfies 1.45 to 1.60, non-uniformity of coating between particles is eliminated, excessive coating on the second positive active material is suppressed, and a uniform coating is induced, thereby reducing resistance and improving initial charge / discharge efficiency and long-term life characteristics.

[0039] Meanwhile, in one embodiment, the method for measuring the cobalt content relative to the total amount of nickel and cobalt on the surface of the positive electrode active material may be obtained by performing scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDS) on the surface of the positive electrode active material, determining the content of nickel and cobalt respectively through quantitative analysis, and then calculating the ratio of the cobalt content to the sum. In addition to SEM-EDS, inductively coupled plasma-mass spectrometry (ICP-MS) or inductively coupled plasma optical emission spectroscopy (ICP-OES) may be used as methods for measuring the cobalt content.

[0040] The average particle size of the second positive active material, that is, the average particle size of a single particle, may be 0.1 μm to 10 μm, for example, 0.1 μm to 7 μm, 0.5 μm to 6 μm, or 1 μm to 5 μm. The particle size of the second positive active material may be smaller than that of the first positive active material, and accordingly, the density of the positive active material may be further increased. Here, the average particle size of the second positive active material may be determined by randomly selecting about 20 active materials in the form of single particles from an electron microscope image of the positive active material, measuring their particle sizes, and taking the diameter (D50) of the particle with a cumulative volume of 50 volume% in the particle size distribution as the average particle size.

[0041] The second cathode active material may be a high-nickel cathode active material containing a high amount of nickel. In the lithium nickel-based composite oxide, the nickel content may be 70 mol% or more based on the total amount of elements excluding lithium and oxygen, for example, 75 mol% or more, 80 mol% or more, 85 mol% or more, or 90 mol% or more, and 99.9 mol% or less, or 99 mol% or less. Such a high-nickel second cathode active material can achieve high capacity and high performance.

[0042] Specifically, the first positive electrode active material and the second positive electrode active material may each independently include a lithium nickel-based composite oxide represented by the following chemical formula 1.

[0043] [Chemical Formula 1]

[0044] Li a1 Ni x1 M 1 y1 M 2 z1 O 2-b1 X b1

[0045] In the above chemical formula 1, 0.9≤a1≤1.8, 0.7≤x1≤1, 0≤y1≤0.3, 0≤z1≤0.2, 0.9≤x1+y1+z1≤1.1, and 0≤b1≤0.1, and M 1 and M 2Each is independently one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is one or more elements selected from the group consisting of F, P, and S.

[0046] In the above chemical formula 1, 0.8≤x1≤1, 0≤y1≤0.2, and 0≤z1≤0.15, or 0.9≤x1≤1, 0≤y1≤0.1, and 0≤z1≤0.1.

[0047] For example, the first positive electrode active material and the second positive electrode active material may each independently include a lithium nickel-based complex oxide represented by Chemical Formula 2 below. The compound represented by Chemical Formula 2 can be described as a lithium nickel cobalt-based complex oxide.

[0048] [Chemical Formula 2]

[0049] Li a2 Ni x2 Co y2 M 3 z2 O 2-b2 X b2

[0050] In the above chemical formula 2, 0.9≤a2≤1.8, 0.7≤x2<1, 0 <y2≤0.3, 0≤z2≤0.2, 0.9≤x2+y2+z2≤1.1, 및 0≤b2≤0.1이고 M 3 is one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is one or more elements selected from the group consisting of F, P, and S.

[0051] In the above chemical formula 2, 0.8≤x2≤0.99, 0.01≤y2≤0.2, and 0.01≤z2≤0.15, or 0.9≤x2≤0.99, 0.01≤y2≤0.1, and 0.01≤z2≤0.1.

[0052] For example, the first positive electrode active material and the second positive electrode active material may each independently include a lithium nickel-based complex oxide represented by the following chemical formula 3. The compound of chemical formula 3 may be lithium nickel-cobalt-aluminum oxide or lithium nickel-cobalt-manganese oxide.

[0053] [Chemical Formula 3]

[0054] Li a3 Ni x3 Co y3 M 4 z3 M 5 w3 O 2-b3 X b3

[0055] In the above chemical formula 3, 0.9≤a3≤1.8, 0.7≤x3≤0.98, 0.01≤y3≤0.29, 0.01≤z3≤0.29, 0≤w3≤0.19, 0.9≤x3+y3+z3+w3≤1.1, and 0≤b3≤0.1, and M 4 is one or more elements selected from the group consisting of Al, and Mn, and M 5 is one or more elements selected from the group consisting of B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is one or more elements selected from the group consisting of F, P, and S.

[0056] In the above chemical formula 3, 0.85≤x3≤0.98, 0.01≤y3≤0.14, 0.01≤z3≤0.14, and 0≤w3≤0.14, or 0.9≤x3≤0.98, 0.01≤y3≤0.09, 0.01≤z3≤0.09, and 0≤w3≤0.09.

[0057] In a positive electrode active material according to one embodiment, with respect to the total amount of the first positive electrode active material and the second positive electrode active material, the first positive electrode active material may be included in an amount of 50% to 90% by weight, and the second positive electrode active material may be included in an amount of 10% to 50% by weight. The first positive electrode active material may be included, for example, in an amount of 60% to 90% by weight, or 70% to 90% by weight, and the second positive electrode active material may be included in an amount of 10% to 40% by weight, or 10% to 30% by weight. When the content ratio of the first positive electrode active material and the second positive electrode active material is such, the positive electrode active material containing it can achieve a high capacity, improve composite density, and exhibit a high energy density.

[0058] Method for manufacturing positive electrode active material

[0059] In one embodiment, a method for manufacturing a positive electrode active material for a lithium secondary battery is provided, comprising: a first positive electrode active material in the form of secondary particles formed by aggregating a plurality of primary particles containing a lithium nickel-based composite oxide having a nickel content of 70 mol% or more relative to all elements excluding lithium and oxygen; a second positive electrode active material in the form of a single particle containing a lithium nickel-based composite oxide having a nickel content of 70 mol% or more relative to all elements excluding lithium and oxygen; cobalt sulfate (CoSO4·7H2O(OH)2) and sodium hydroxide (NaOH) being introduced into a solvent and mixed; removing the solvent; adding a lithium raw material to the product; and heat treating to obtain the aforementioned positive electrode active material.

[0060] Through the above manufacturing method, a positive active material can be obtained by mixing a first positive active material comprising a coating portion existing in the form of a film on the surface of the secondary particle and a second positive active material comprising a coating portion existing in the form of a film on the surface of the single particle. The coating portion is characterized by comprising a composite phase of lithium cobalt oxide and cobalt oxyhydroxide.

[0061] The description of the above lithium nickel-based composite oxide is omitted as it is as previously stated. The above solvent may be an aqueous solvent such as water or an alcohol-based solvent.

[0062] The first positive active material and the second positive active material can be mixed in a weight ratio of 9:1 to 5:5, for example, in a weight ratio of 8:2 to 6:4. In this case, it is advantageous to achieve high capacity and high energy density.

[0063] The above cobalt sulfate may be a coating raw material introduced to manufacture a positive electrode active material according to one embodiment. The above cobalt sulfate may be mixed such that the content of cobalt relative to elements excluding lithium and oxygen in the entire lithium nickel-based composite oxide of the first positive electrode active material and the lithium nickel-based composite oxide of the second positive electrode active material is 0.5 mol to 5 mol, for example, 0.5 mol to 4 mol, or 1 mol to 3 mol.

[0064] The above sodium hydroxide can act as a precipitating agent and / or a pH regulator. If sodium hydroxide is not added, the coating layer may not be effectively formed or the desired amount of cobalt may not be coated, and the CoOOH phase may not appear on the coating layer of the final anode active material surface.

[0065] The sodium hydroxide above may be added such that the sodium content is 1 to 10 moles per 100 moles of the total elements excluding lithium and oxygen in the lithium nickel-based composite oxide of the first positive electrode active material and the lithium nickel-based composite oxide of the second positive electrode active material, for example, 3 to 9 moles, or 5 to 8 moles. When the sodium content added satisfies the above range, a film-type coating containing LiCoO2 and CoOOH can be effectively formed.

[0066] In addition, the ratio of the cobalt molar content of cobalt sulfate to the sodium molar content of sodium hydroxide may be 1:1.1 to 1:5, for example, 1:1.5 to 1:4, or 1:2 to 1:3. When the molar ratio of cobalt and sodium to be added satisfies the above range, it is advantageous to form a film-type coating containing LiCoO2 and CoOOH.

[0067] After removing the solvent, a lithium raw material is added to the product, wherein the lithium raw material may be, for example, Li2CO3, LiOH, hydrates thereof, or a combination thereof. The lithium raw material may be added such that the lithium content relative to elements excluding lithium and oxygen in the entire lithium nickel-based composite oxide of the first cathode active material and the lithium nickel-based composite oxide of the second cathode active material is 0.1 mol to 10 mol, for example, 0.1 mol to 8 mol, or 1 mol to 6 mol. During the process of washing and coating the cathode active material in the solvent as described above, damage may occur to the surface of the lithium nickel-based composite oxide particles, resulting in a decrease in capacity and rate characteristics and an increase in resistance during high-temperature storage. However, by adding the lithium raw material during heat treatment in this manner, the surface damage can be repaired and the capacity and rate characteristics can be improved.

[0068] The above heat treatment may be carried out in an oxidizing gas atmosphere, such as an oxygen or air atmosphere, and may be performed at 650°C to 900°C, or at 650°C to 800°C. The heat treatment time may vary depending on the heat treatment temperature, but may be performed for, for example, for 5 to 30 hours or for 10 to 24 hours. By performing the heat treatment under the above conditions, a coating portion having a composite phase of lithium cobalt oxide and cobalt oxyhydroxide can be formed.

[0069] According to one embodiment, mixing a first positive active material, a second positive active material, cobalt sulfate, and sodium hydroxide in a solvent may be performed by first carrying out a first process of adding and mixing the second positive active material, cobalt sulfate, and sodium hydroxide in a solvent, and then sequentially carrying out a second process of adding and mixing the first positive active material, cobalt sulfate, and sodium hydroxide therein. According to this method, excessive coating on the single particle is suppressed while the coating on the secondary particle is strengthened, that is, the relationship between the coating content of the two types of particles is appropriately controlled, thereby improving the performance of the lithium secondary battery, such as high-temperature long-term life characteristics, initial charge / discharge efficiency, and high-temperature storage performance. For example, according to the above sequential process, a positive electrode active material can be manufactured such that the ratio of the content of cobalt (at%) to the total amount of nickel and cobalt in the cobalt coating portion of the first positive electrode active material to the content of cobalt (at%) to the total amount of nickel and cobalt in the cobalt coating portion of the second positive electrode active material satisfies 1.45 to 1.60.

[0070] In addition, the time required for the first process may be about 10 minutes to about 100 minutes, and the time required for the second process may be about 10 minutes to about 100 minutes. Also, the ratio of the time required for the first process (minute) to the time required for the second process (minute) may be 50:50 to 75:25, for example, 65:35 to 75:25. By designing with such a time ratio, the coating content of each of the first positive active material and the second positive active material can be optimized.

[0071] anode

[0072] A positive electrode for a lithium secondary battery may include a current collector and a positive electrode active material layer located on the current collector. The positive electrode active material layer may include a positive electrode active material and may further include a binder and / or a conductive material.

[0073] The above binder serves to adhere the positive active material particles well to each other and also to adhere the positive active material well to the current collector. Representative examples include polyvinyl alcohol, carboxymethylcellulose, hydroxypropylcellulose, diacetylcellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc., but are not limited thereto.

[0074] The content of the binder in the above positive active material layer may be approximately 1% to 5% by weight with respect to the total weight of the positive active material layer.

[0075] The above conductive material is used to impart conductivity to the electrode, and any electronically conductive material that does not cause chemical changes can be used in the battery being constructed. Examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube; metal-based materials containing copper, nickel, aluminum, silver, etc., in the form of metal powder or metal fiber; conductive polymers such as polyphenylene derivatives; or conductive materials comprising a mixture thereof.

[0076] The content of the conductive material in the above positive active material layer may be 1% to 5% by weight relative to the total weight of the positive active material layer.

[0077] Aluminum foil may be used as the anode current collector, but is not limited thereto.

[0078] cathode

[0079] A negative electrode for a lithium secondary battery comprises a current collector and a negative electrode active material layer located on the current collector. The negative electrode active material layer comprises a negative electrode active material and may further comprise a binder and / or a conductive material.

[0080] The above-mentioned negative electrode active material includes a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and dedoping lithium, or a transition metal oxide.

[0081] A material capable of reversibly intercalating / deintercalating the lithium ions may include a carbon-based negative electrode active material, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, calcined coke, etc.

[0082] As the above lithium metal alloy, an alloy of a metal selected from the group consisting of lithium, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn may be used.

[0083] As a material capable of doping and undoping the above lithium, a Si-based negative electrode active material or a Sn-based negative electrode active material may be used, and the Si-based negative electrode active material may include silicon, a silicon-carbon composite, or SiO₂. xExamples of the above Sn-based negative electrode active materials include (0 < x < 2), Si-Q alloy (where Q is an element selected from the group consisting of alkali metals, alkaline earth metals, group 13 elements, group 14 elements, group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof, and is not Si), Sn, SnO2, Sn-R alloy (where R is an element selected from the group consisting of alkali metals, alkaline earth metals, group 13 elements, group 14 elements, group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof, and is not Sn), and at least one of these may be mixed with SiO2. The above elements Q and R may be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0084] The silicon-carbon composite may be, for example, a silicon-carbon composite comprising a core containing crystalline carbon and silicon particles and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. As the amorphous carbon precursor, coal-based pitch, mesophase pitch, petroleum-based pitch, coal-based oil, petroleum-based heavy oil, or polymer resins such as phenolic resin, furan resin, or polyimide resin may be used. In this case, the silicon content may be 10% to 50% by weight of the total weight of the silicon-carbon composite. Additionally, the content of the crystalline carbon may be 10% to 70% by weight of the total weight of the silicon-carbon composite, and the content of the amorphous carbon may be 20% to 40% by weight of the total weight of the silicon-carbon composite. Furthermore, the thickness of the amorphous carbon coating layer may be 5nm to 100nm. The average particle size (D50) of the silicon particles may be 10 nm to 20 μm. The average particle size (D50) of the silicon particles may preferably be 10 nm to 200 nm. The silicon particles may exist in an oxidized form, wherein the atomic content ratio of Si:O within the silicon particles indicating the degree of oxidation may be 99:1 to 33:67. The silicon particles are SiO x It can be a particle, and in this case, SiO x In this specification, the range of x may be greater than 0 and less than 2. Unless otherwise defined, the average particle size (D50) refers to the diameter of a particle in which the cumulative volume in the particle size distribution is 50 volume%.

[0085] The above Si-based negative electrode active material or Sn-based negative electrode active material may be used in combination with a carbon-based negative electrode active material. When the Si-based negative electrode active material or Sn-based negative electrode active material and the carbon-based negative electrode active material are mixed and used, the mixing ratio may be 1:99 to 90:10 by weight.

[0086] The content of the negative electrode active material in the above negative electrode active material layer may be 95% to 99% by weight with respect to the total weight of the negative electrode active material layer.

[0087] In one embodiment, the negative active material layer further comprises a binder and optionally further comprises a conductive material. The content of the binder in the negative active material layer may be 1% to 5% by weight with respect to the total weight of the negative active material layer. Additionally, when further comprising a conductive material, the negative active material layer may comprise 90% to 98% by weight of the negative active material, 1% to 5% by weight of the binder, and 1% to 5% by weight of the conductive material.

[0088] The above binder serves to effectively bond the negative electrode active material particles to each other and also to effectively bond the negative electrode active material to the current collector. As the binder, a water-insoluble binder, a water-soluble binder, or a combination thereof may be used.

[0089] Examples of the above-mentioned water-insoluble binders include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, an ethylene propylene copolymer, polystyrene, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0090] Examples of the above water-soluble binders include rubber-based binders or polymer resin binders. The rubber-based binder may be selected from styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, and combinations thereof. The polymer resin binder may be selected from polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, ethylenepropylenediene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.

[0091] When a water-soluble binder is used as the above-mentioned cathode binder, a cellulose-based compound capable of imparting viscosity may be further included. As this cellulose-based compound, one or more types such as carboxymethyl cellulose, hydroxypropylmethyl cellulose, methyl cellulose, or alkali metal salts thereof may be mixed and used. Na, K, or Li may be used as the alkali metal. The content of such a thickener may be 0.1 to 3 parts by weight per 100 parts by weight of the cathode active material.

[0092] The above conductive material is used to impart conductivity to the electrode, and any electronically conductive material that does not cause chemical changes can be used in the battery being constructed. Examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube; metal-based materials in the form of metal powder or metal fibers including copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or conductive materials including mixtures thereof.

[0093] The above-mentioned cathode current collector may be selected from the group consisting of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0094] lithium secondary battery

[0095] Another embodiment provides a lithium secondary battery comprising a positive electrode, a negative electrode, a separator located between the positive electrode and the positive electrode, and an electrolyte.

[0096] FIG. 1 is a schematic diagram illustrating a lithium secondary battery according to one embodiment. Referring to FIG. 1, a lithium secondary battery (100) according to one embodiment comprises a battery cell including a positive electrode (114), a negative electrode (112) positioned opposite to the positive electrode (114), a separator (113) disposed between the positive electrode (114) and the negative electrode (112), and an electrolyte for a lithium secondary battery impregnating the positive electrode (114), the negative electrode (112), and the separator (113); a battery container (120) containing the battery cell; and a sealing member (140) sealing the battery container (120).

[0097] The above electrolyte includes a non-aqueous organic solvent and a lithium salt.

[0098] The above-mentioned non-aqueous organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Carbonate-based, ester-based, ether-based, ketone-based, alcohol-based, or aprotic solvents may be used as non-aqueous organic solvents. As for the above-mentioned carbonate-based solvents, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. may be used. The above ester-based solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methylpropionate, ethylpropionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, etc. The above ether-based solvents may include dibutyl ether, tetraglyme, deglyme, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, etc., and the above ketone-based solvents may include cyclohexanone, etc. In addition, the above alcohol-based solvent may include ethyl alcohol, isopropyl alcohol, etc., and the above aprotic solvent may include nitriles such as R-CN (wherein R is a C2 to C20 straight-chain, branched, or cyclic hydrocarbon group and may include double bonds, aromatic rings, or ether bonds), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes.

[0099] The above-mentioned non-aqueous organic solvents may be used alone or in a mixture of one or more. When used in a mixture of one or more, the mixing ratio can be appropriately adjusted according to the desired battery performance, which is widely understood by those engaged in the relevant field.

[0100] In addition, the above carbonate-based solvent may be used by mixing cyclic carbonates and chain carbonates. In this case, when the cyclic carbonates and chain carbonates are mixed in a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte may be excellent.

[0101] The above-mentioned non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent in addition to the carbonate-based solvent. In this case, the carbonate-based solvent and the aromatic hydrocarbon organic solvent may be mixed in a volume ratio of about 1:1 to about 30:1.

[0102] As the above aromatic hydrocarbon solvent, an aromatic hydrocarbon compound of the following chemical formula I may be used.

[0103] [Chemical Formula I]

[0104]

[0105] In the above chemical formula I, R 4 to R 9 The groups are identical or different from each other and are selected from the group consisting of hydrogen, halogen, alkyl groups having 1 to 10 carbon atoms, haloalkyl groups having 1 to 10 carbon atoms, and combinations thereof.

[0106] Specific examples of the above aromatic hydrocarbon solvents include benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, fluorotoluene, 2,3-difluorotoluene, 2,4-difluorotoluene. It is selected from the group consisting of 2,5-difluorotoluene, 2,3,4-trifluorotoluene, 2,3,5-trifluorotoluene, chlorotoluene, 2,3-dichlorotoluene, 2,4-dichlorotoluene, 2,5-dichlorotoluene, 2,3,4-trichlorotoluene, 2,3,5-trichlorotoluene, iodotoluene, 2,3-diiodotoluene, 2,4-diiodotoluene, 2,5-diiodotoluene, 2,3,4-triiodotoluene, 2,3,5-triiodotoluene, xylene, and combinations thereof.

[0107] The above electrolyte may further include vinylene carbonate or an ethylene carbonate-based compound of the following chemical formula II as a life-enhancing additive to improve battery life.

[0108] [Chemical Formula II]

[0109]

[0110] In the above chemical formula II, R 10 and R 11 The groups are identical or different from each other and are selected from the group consisting of hydrogen, halogen groups, cyano groups, nitro groups, and fluorinated C1 to C5 alkyl groups, and the R 10 and R 11 At least one of the groups is selected from the group consisting of halogen groups, cyano groups, nitro groups, and fluorinated C1 to C5 alkyl groups, provided that R 10 and R11 Not all of them are hydrogen.

[0111] Representative examples of the above-mentioned ethylene carbonate-based compounds include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, or fluoroethylene carbonate. When using more of these lifespan-enhancing additives, the amount used can be appropriately controlled.

[0112] The above lithium salt is a material that is dissolved in a non-aqueous organic solvent and acts as a source of lithium ions within the battery, enabling the operation of a basic lithium secondary battery and facilitating the movement of lithium ions between the positive and negative electrodes.

[0113] Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, and LiN(C x F 2x+1 SO2)(C y F 2y+1 One or more selected from the group consisting of SO2)(where x and y are natural numbers, for example, integers from 1 to 20), lithium difluoro(bisoxalato) phosphate, LiCl, LiI, LiB(C2O4)2 (lithium bis(oxalato) borate; LiBOB), and lithium difluoro(oxalato) borate (LiDFOB).

[0114] It is preferable to use a lithium salt concentration within the range of 0.1M to 2.0M. When the lithium salt concentration falls within the above range, the electrolyte has appropriate conductivity and viscosity, so it can exhibit excellent electrolyte performance and lithium ions can move effectively.

[0115] The separator (113) separates the positive electrode (114) and the negative electrode (112) and provides a pathway for the movement of lithium ions; any separator commonly used in lithium-ion batteries can be used. That is, a separator with low resistance to the movement of electrolyte ions and excellent electrolyte moisture retention capacity can be used. For example, the separator (113) may include glass fiber, polyester, polyethylene, polypropylene, polytetrafluoroethylene, or a combination thereof, and may be in the form of a non-woven fabric or a woven fabric. For example, polyolefin-based polymer separators such as polyethylene and polypropylene are mainly used in lithium-ion batteries, and a coated separator containing ceramic components or polymer materials may be used to ensure heat resistance or mechanical strength, and may optionally be used in a single-layer or multi-layer structure.

[0116] Lithium secondary batteries can be classified into lithium-ion batteries, lithium-ion polymer batteries, and lithium polymer batteries depending on the type of separator and electrolyte used, and can be classified into cylindrical, prismatic, coin, and pouch types depending on their shape, and into bulk and thin-film types depending on their size. Since the structure and manufacturing methods of these batteries are widely known in this field, a detailed description is omitted.

[0117] A lithium secondary battery according to one embodiment can be used in electric vehicles (EVs), hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs), and portable electronic devices, as it has high capacity and excellent storage stability, lifespan characteristics, and high rate characteristics at high temperatures.

[0118] Examples and comparative examples of the present invention are described below. The following examples are merely illustrative of the present invention, and the present invention is not limited to the following examples.

[0119] Example 1

[0120] 1. Preparation of a first lithium-nickel-based composite oxide in the form of secondary particles

[0121] As metal raw materials, nickel sulfate (NiSO4·6H2O), cobalt sulfate (CoSO4·7H2O), and aluminum sulfate (Al2(SO4)3·18H2O) were dissolved in distilled water as a solvent in a molar ratio of 91:8:1 to prepare a mixed solution, and ammonia water (NH4OH) and sodium hydroxide (NaOH) were prepared as a precipitating agent to form a complex compound.

[0122] After introducing a diluted ammonia solution into a continuous reactor, a mixed solution of metal raw materials is continuously fed in, and sodium hydroxide is added to maintain the pH inside the reactor. The reaction is carried out slowly for approximately 80 hours, and once the reaction stabilizes, the overflowing product is collected and subjected to washing and drying processes to obtain the final precursor. Accordingly, a primary nickel-based hydroxide (Ni) in the form of secondary particles formed by the aggregation of primary particles is produced. 0.91 Co 0.08 Al 0.01 (OH)2) is obtained, washed, and dried.

[0123] By mixing the first nickel-based hydroxide with LiOH so that the molar ratio of lithium to the total metal amount of the first nickel-based hydroxide is 1.04, and performing a first heat treatment at approximately 750°C for 15 hours in an oxygen atmosphere, the first lithium nickel-based oxide (LiNi 0.91 Co 0.08 Al 0.01 O2) is obtained. The average particle size of the obtained first lithium nickel-based oxide is approximately 15 μm, and it is in the form of secondary particles formed by the aggregation of primary particles.

[0124] 2. Preparation of Second Lithium Nickel-Based Composite Oxide in Single-Particle Form

[0125] A mixed solution is prepared by dissolving nickel sulfate, cobalt sulfate, and manganese sulfate (MnSO4·H2O) in distilled water, the solvent, in a molar ratio of 95:4:1. To form a complex, a diluted solution of ammonia water (NH4OH) and sodium hydroxide (NaOH) are prepared as a precipitating agent. Subsequently, the metal raw material mixed solution, ammonia water, and sodium hydroxide are each introduced into the reactor. Next, the reaction is carried out for approximately 20 hours while stirring. Afterward, the slurry solution in the reactor is filtered, washed with high-purity distilled water, and dried for 24 hours to produce a secondary nickel-based hydroxide (Ni 0.95 Co 0.04 Mn 0.01 (OH)2) powder is obtained. The obtained nickel-based hydroxide powder has an average particle size of approximately 4.0 μm, and a specific surface area of ​​approximately 15 m² as measured by BET. 2 / g is.

[0126] The obtained second nickel-based hydroxide, LiOH satisfying Li / (Ni+Co+Mn) = 1.05, and Al, Zr, and Mg components as dopants are mixed together and introduced into a calcination furnace, and a second heat treatment is performed at 820 °C for 10 hours in an oxygen atmosphere. Afterwards, the obtained product is crushed for about 30 minutes to separate and disperse it into a number of second lithium nickel-based oxides having a single particle form. The average particle size of the obtained second lithium nickel-based oxides in a single particle form is about 3.7 μm.

[0127] 3. Cobalt Coating and Preparation of Final Anode Active Material

[0128] A first process is carried out in which distilled water solvent and cobalt sulfate (CoSO4·7H2O) are introduced into a mixer, and the prepared second lithium-nickel-based composite oxide is introduced and mixed. The cobalt sulfate is introduced such that the cobalt content relative to the total elements excluding lithium and oxygen in the second lithium-nickel-based composite oxide is 3.0 molar parts. In the first process, after introducing the second lithium-nickel-based composite oxide, sodium hydroxide, which acts as a precipitating agent and a pH regulator, is introduced together and mixed. Sodium hydroxide is introduced such that the sodium content relative to 100 molar parts of the total elements excluding lithium and oxygen in the second lithium-nickel-based composite oxide is 6.0 molar parts.

[0129] After carrying out the first process for 30 minutes, a second process is carried out in which cobalt sulfate is added, followed by the addition and mixing of the first lithium-nickel-based composite oxide. The first lithium-nickel-based composite oxide is added so that the weight ratio of the first lithium-nickel-based composite oxide to the previously added second lithium-nickel-based composite oxide is 7:3. The cobalt sulfate is added so that the cobalt content relative to the total elements excluding lithium and oxygen in the first lithium-nickel-based composite oxide is 3.0 molar parts. In the second process as well, sodium hydroxide is added and mixed together after the first lithium-nickel-based composite oxide is added. Sodium hydroxide is added so that the sodium content relative to 100 molar parts of the total elements excluding lithium and oxygen in the first lithium-nickel-based composite oxide is 6.0 molar parts.

[0130] After carrying out the second process for 30 minutes, the mixture is filtered and dried at 200°C for 10 hours. Subsequently, the resulting product is mixed with lithium hydroxide and placed into a calcination furnace, and heat-treated at approximately 700°C for 15 hours in an oxygen atmosphere. At this time, lithium hydroxide is added such that the lithium content is 6 molar parts relative to the total elements excluding lithium and oxygen in the resulting product. Afterward, the calcination furnace is cooled to room temperature to obtain a final positive active material in which a first positive active material, comprising a film-shaped coating formed on the surface of a secondary particle consisting of a first lithium-nickel-based composite oxide, and a second positive active material, comprising a film-shaped coating formed on the surface of a single particle consisting of a second lithium-nickel-based composite oxide, are mixed.

[0131] 4. Manufacture of the anode

[0132] A positive electrode active material slurry is prepared by mixing 95% by weight of the final positive electrode active material, 3% by weight of a polyvinylidene fluoride binder, and 2% by weight of a carbon nanotube conductive material in an N-methylpyrrolidone solvent. The positive electrode active material slurry is applied to an aluminum current collector, dried, and then rolled to prepare a positive electrode.

[0133] 5. Manufacture of lithium secondary batteries

[0134] A coin half-cell is manufactured by using a prepared positive electrode and a lithium metal counter electrode, interposing a separator with a polyethylene polypropylene multilayer structure between them, and injecting an electrolyte solution in which 1.0 M LiPF6 lithium salt is added to a solvent mixed with ethylene carbonate and diethyl carbonate in a 50:50 volume ratio.

[0135] Comparative Example 1

[0136] In “3. Preparation of Cobalt Coating and Final Anode Active Material” of Example 1, an anode active material, an anode, and a coin half-cell are prepared in the same manner as in Example 1, except that sodium hydroxide, which acts as a precipitating agent and a pH regulator in the first and second processes, is not added.

[0137] Comparative Example 2

[0138] In “3. Preparation of Cobalt Coating and Final Cathode Active Material” of Example 1, the coating is performed dry rather than wet. That is, the first lithium-nickel composite oxide, the second lithium-nickel composite oxide, cobalt hydroxide, and lithium hydroxide are mixed in a kiln and heat-treated at 700°C for 15 hours. At this time, cobalt hydroxide is added so that the cobalt content relative to all elements excluding lithium and oxygen in the first lithium-nickel composite oxide and the second lithium-nickel composite oxide is 3.0 molar, and lithium hydroxide is added so that the lithium content is 6.0 molar. Otherwise, the cathode active material, cathode, and coin half-cell are prepared in the same manner as in Example 1.

[0139] Evaluation Example 1: X-ray Diffraction Analysis

[0140] X-ray diffraction analysis was performed on (i) the final positive electrode active material prepared in Example 1, (ii) the positive electrode plate obtained by disassembling the battery immediately before operating the coin half-cell of Example 1, and (iii) the positive electrode plate obtained by disassembling the battery after running the coin half-cell of Example 1 for 150 cycles, and the results are shown in FIG. 2.

[0141] In (iii) above, the coin half cell of Example 1 was initially charged under constant current (0.2 C) and constant voltage (4.25 V, 0.05 C cut-off) conditions, rested for 10 minutes, then initially discharged under constant current (0.2 C) conditions until it reached 3.0 V, and then repeated 150 charge-discharge cycles at 45°C at 0.5 C / 0.5 C.

[0142] Figure 3 is an enlarged view of the graph at approximately 20° in Figure 2, and Figure 4 is an enlarged view of the graph at approximately 40° in Figure 2. Figure 5 is an X-ray diffraction analysis graph for Co(OH)2, CoOOH, and Co3O4 for comparison.

[0143] Referring to FIGS. 2 to 5, the positive active material according to Example 1 exhibits peaks at 19.5° to 20.5° and at 39° to 40°, indicating that CoOOH is present on the surface. In other words, it can be confirmed that a composite phase of a LiCoO2-like structure and CoOOH exists in the surface coating portion of the positive active material of Example 1. This composite phase is captured not only in the manufactured positive active material but also after it is manufactured into a positive electrode plate and after the battery is operated.

[0144] X-ray diffraction analysis was performed in the same manner for Comparative Example 1 and Comparative Example 2, but in the case of Comparative Example 1, quantitative coating was not achieved and the CoOOH phase was not detected in the X-ray diffraction graph. In the case of Comparative Example 2, continuous coating was not achieved on the surface of the positive electrode active material and the CoOOH phase was not detected in the X-ray diffraction graph.

[0145] Evaluation Example 2: SEM-EDS analysis of the cross-section of the cathode active material

[0146] Figure 6 is an SEM-EDS analysis image of a cross-section of a particle corresponding to the first cathode active material in the final cathode active material prepared in Example 1. Figure 7 is an SEM-EDS analysis image of a cross-section of a particle corresponding to the second cathode active material in the final cathode active material prepared in Example 1. The highlighted portion in Figures 6 and 7 represents cobalt.

[0147] Referring to Fig. 6, it can be seen that a coating containing cobalt exists in the form of a film on the surface of the secondary particle, and that cobalt is also coated on the grain boundaries, which are the surfaces of the primary particles existing inside the secondary particle. Referring to Fig. 7, it can be seen that a coating containing cobalt is also formed in the form of a film on the surface of the single particle.

[0148] Evaluation Example 3: Analysis of Cobalt Coating Content of Anode Active Material

[0149] The cobalt content (Co / (Ni+Co), at%) on the surface of each of the first and second positive active materials was measured through SEM-EDS analysis performed in Evaluation Example 2 above, and the results are shown in Table 1 below.

[0150] 1st positive active material coating content (A) Second positive active material coating content (B) A / B Example 1 61.8 40.4 1.53

[0151] Evaluation Example 4: Battery Performance Evaluation

[0152] Three samples of the lithium secondary batteries prepared in Example 1, Comparative Example 1, and Comparative Example 2 were prepared, and the initial charge and discharge were performed under conditions of constant current (0.2 C) and constant voltage (4.25 V, 0.05 C cut-off), and after resting for 10 minutes, the batteries were discharged under constant current (0.2 C) conditions until the voltage reached 3.0 V. Subsequently, the life characteristics were evaluated by repeating 50 charge and discharge cycles at 0.5 C / 0.5 C at 45°C, and the capacity retention rate at each cycle relative to the initial discharge capacity is shown in FIG. 8.

[0153] Referring to Fig. 8, it can be seen that the lifespan characteristics of Example 1 are superior to those of Comparative Example 1 and Comparative Example 2.

[0154] Although preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements by those skilled in the art using the basic concepts defined in the following claims are also included within the scope of the present invention. Explanation of the symbols

[0155] 100: Lithium secondary battery 112: Negative electrode 113: Separator 114: Anode 120: Battery container 140: Encapsulation member

Claims

Claim 1 A positive active material for a lithium secondary battery comprising a first positive active material in the form of a secondary particle formed by the aggregation of a plurality of primary particles, and a second positive active material in the form of a single particle, wherein the first positive active material and the second positive active material each comprise a lithium nickel-based composite oxide having a nickel content of 70 mol% or more relative to all elements excluding lithium and oxygen, the first positive active material comprises a coating portion existing in the form of a film on the surface of the secondary particle, and the second positive active material comprises a coating portion existing in the form of a film on the surface of the single particle, wherein the coating portion of the first positive active material and the coating portion of the second positive active material each comprise lithium cobalt oxide and cobalt oxyhydroxide. Claim 2 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the lithium cobalt oxide and the cobalt oxyhydroxide exist in a composite phase in the coating portion of the first positive electrode active material and the coating portion of the second positive electrode active material. Claim 3 A positive active material for a lithium secondary battery according to claim 1, wherein the positive active material exhibits peaks at 19.5° to 20.5° and 39° to 40° in X-ray diffraction analysis. Claim 4 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the thickness of each of the coating portion of the first positive electrode active material and the coating portion of the second positive electrode active material is 1 nm to 500 nm. Claim 5 A positive electrode active material for a lithium secondary battery according to claim 1, wherein, in the entire positive electrode active material, the content of surface cobalt relative to 100 mol% of elements excluding lithium and oxygen in a lithium nickel-based composite oxide is 0.5 mol% to 5 mol%. Claim 6 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the ratio of the content of cobalt (at%) relative to the total amount of nickel and cobalt in the coating portion of the first positive electrode active material to the content of cobalt (at%) relative to the total amount of nickel and cobalt in the coating portion of the second positive electrode active material is 1.45 to 1.

60. Claim 7 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the content of cobalt relative to the total amount of nickel and cobalt in the coating portion of the first positive electrode active material is 55 at% to 70 at%. Claim 8 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the content of cobalt relative to the total amount of nickel and cobalt in the coating portion of the second positive electrode active material is 39 at% to 45 at%. Claim 9 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the first positive electrode active material further comprises a grain boundary coating portion located on the surface of primary particles inside the secondary particles, and the grain boundary coating portion comprises lithium cobalt oxide and cobalt oxyhydroxide. Claim 10 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the average particle size of the first positive electrode active material is 5 μm to 20 μm and the average particle size of the second positive electrode active material is 0.1 μm to 10 μm. Claim 11 A positive electrode active material for a lithium secondary battery according to claim 1, wherein, with respect to the total amount of the first positive electrode active material and the second positive electrode active material, the first positive electrode active material is included in an amount of 50% to 90% by weight and the second positive electrode active material is included in an amount of 10% to 50% by weight. Claim 12 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the lithium nickel-based composite oxide of the first positive electrode active material and the lithium nickel-based composite oxide of the second positive electrode active material are each independently represented by the following chemical formula 1: [Chemical Formula 1]Li a1 Ni x1 M 1 y1 M 2 z1 O 2-b1 X b1 In the above chemical formula 1, 0.9≤a1≤1.8, 0.7≤x1≤1, 0≤y1≤0.3, 0≤z1≤0.2, 0.9≤x1+y1+z1≤1.1, and 0≤b1≤0.1, and M 1 and M 2 Each is independently one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sr, Ti, V, W, and Zr, and X is one or more elements selected from the group consisting of F, P, and S. Claim 13 A method for manufacturing a positive electrode active material for a lithium secondary battery, comprising: a first positive electrode active material in the form of secondary particles formed by aggregating a plurality of primary particles containing a lithium nickel-based composite oxide having a nickel content of 70 mol% or more relative to all elements excluding lithium and oxygen; a second positive electrode active material in the form of a single particle containing a lithium nickel-based composite oxide having a nickel content of 70 mol% or more relative to all elements excluding lithium and oxygen; adding and mixing cobalt sulfate and sodium hydroxide in a solvent; removing the solvent; adding a lithium raw material to the product; and heat treating to obtain a positive electrode active material according to any one of claims 1 to 12. Claim 14 A method for manufacturing a positive electrode active material for a lithium secondary battery according to claim 13, wherein the first positive electrode active material and the second positive electrode active material are mixed in a weight ratio of 9:1 to 5:

5. Claim 15 A method for manufacturing a positive electrode active material for a lithium secondary battery according to claim 13, wherein the above cobalt sulfate is mixed such that the content of cobalt is 0.5 mol to 5 mol per 100 mol of all elements excluding lithium and oxygen in the entire lithium nickel-based composite oxide of the first positive electrode active material and the lithium nickel-based composite oxide of the second positive electrode active material. Claim 16 A method for manufacturing a positive electrode active material for a lithium secondary battery according to claim 13, wherein the sodium hydroxide is mixed such that the sodium content is 1 to 10 moles per 100 moles of all elements excluding lithium and oxygen in the entire lithium nickel-based composite oxide of the first positive electrode active material and the lithium nickel-based composite oxide of the second positive electrode active material. Claim 17 A method for manufacturing a positive electrode active material for a lithium secondary battery according to claim 13, wherein the ratio of the cobalt molar content of the cobalt sulfate to the sodium molar content of the sodium hydroxide is 1:1.1 to 1:

5. Claim 18 A method for manufacturing a positive electrode active material for a lithium secondary battery according to claim 13, wherein the lithium raw material is introduced such that the lithium content relative to elements excluding lithium and oxygen in the entire lithium nickel-based composite oxide of the first positive electrode active material and the lithium nickel-based composite oxide of the second positive electrode active material is 0.1 molar part to 10 molar part. Claim 19 A method for manufacturing a positive electrode active material for a lithium secondary battery, wherein, in claim 13, the heat treatment is carried out in a temperature range of 650 ℃ to 900 ℃. Claim 20 A method for manufacturing a positive electrode active material for a lithium secondary battery according to claim 13, wherein mixing a first positive electrode active material, a second positive electrode active material, cobalt sulfate, and sodium hydroxide in a solvent is performed by first performing a process of mixing the second positive electrode active material, cobalt sulfate, and sodium hydroxide in a solvent, and then sequentially performing a second process of mixing the first positive electrode active material, cobalt sulfate, and sodium hydroxide therein. Claim 21 A method for manufacturing a positive electrode active material for a lithium secondary battery according to claim 20, wherein the ratio of the time required for the first process (minutes) to the time required for the second process (minutes) is 50:50 to 75:

25. Claim 22 A lithium secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, comprising a positive active material according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Positive active material for rechargeable lithium battery, preparing method thereof and rechargeable lithium battery including the same

    EP4095949A1

  • Positive active material for rechargeable lithium battery, method of preparing same and rechargeable lithium battery including same

    KR1020120114955A

  • Positive electrode active material for lithium secondary battery, preparing method of the same, positive electrode and lithium secondary battery including the same

    KR1020190041420A

  • Positive active material for rechargeable lithium battery, method of preparing same and rechargeable lithium battery including same

    KR1020200051101A